Quality air monitoring equipment: the review of air quality monitoring equipment - Rosman, Putri Shazlia; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Mohd. Hussain, Mohd. Ramzi; Azmi, Mohd Zikri (Science and Engineering Research Support Society, 2020)
Air quality is one of the important elements in environmental monitoring such as water quality and noise level monitoring. The result from the in-situ experiment would give direct reading on current existing environment on any propose study area. Nowadays, the invention of air quality equipment is easy to be handle, hand-held, portable and convenience to bring to niche or impossible area to fits in by human. With long life battery allow it operate for 24 hours at field and many divines gases can be monitor with single head. The purpose of the study was to review the equipment that used for air quality monitoring that capable to gives real time reading, cost effective equipment and portable to monitor at site. In this study, Aeroqual Series 500 is an air quality monitoring equipment was used to monitored the PM2.5 and PM10 at three different site studies. The Series 500 air quality is portable handheld monitor and enables to give accurate real time data ether deployed for short term fixed monitoring. The site studies were selected by the environmental consultant to be reviewed. The result of the air quality was accurate in real time respond to monitor air quality. However, another factor such as meteorology condition and topography, slope gradient and land use factor need to be considered to place the equipment in order to avoid any undesirable reading and missing data.